Recurrent Struma Ovarii Presented with High Levels of Thyroglobulin - Christiana Oikonomou; Nikol Spathari; Stavroula Doumoulaki; Antonella Koutela; Christos Stagkoglou; Dimitris Keramidaris (Case Reports in Surgery)
Struma ovarii are rare ovarian tumors, of monodermal germ cell origin, containing predominantly thyroid tissue. They are typically benign unilateral pelvic masses. Among the rare cases of malignancy, the most common histological type is that of the papillary carcinoma. A definite preoperative diagnosis of these tumors is difficult to achieve since most imaging findings are generally nonspecific. A rare exception is the case of synchronous abnormal thyroid blood tests where an ovarian teratoma should be highly suspected, especially when no pathology of the thyroid gland coexists. Surgical excision is the mainstay of treatment. Taking into account that struma ovarii are mainly encountered in patients of a childbearing age, a conservative surgical approach is a reasonable option. We present the case of a 56-year-old woman who was diagnosed with both a primary and recurrent struma ovarii while investigating the incidental finding of elevated blood laboratory levels of the thyroglobulin (Tg).